Utilizing Blockchain for Electronic Wellbeing Records - Sugeng Widada; Warseno; Sugina; Alfian, Sulthan Taqi Sampoerna (Blockchain Frontier Technology, 2022)
Blockchain has been an interesting area of ​​exploration for some time and the advantages it provides have been exploited by a variety of different businesses. Basically, the medical service area has benefited greatly from blockchain innovations due to safety, security, confidentiality and decentralization. Overall, the Electronic Wellbeing Record (EHR) system addresses issues related to information security, honesty and fairness. In this paper, we talk about how blockchain innovation can be used to change the EHR framework and can be the answer to this problem. We present a system that can be used for the implementation of blockchain innovations in the field of medical services for EHR. The essence of our proposed system is first and foremost to implement blockchain innovations for EHR and in addition to provide secure electronic records capacity by characterizing granular access rules for clients of the proposed structure. Moreover, this structure also speaks to the flexibility issue that blockchain innovation sees as a whole through the use of the off-chain capacity of the record. This structure gives the EHR framework the advantage of having a blockchain-based setup that is versatile, secure, and basic. The information on the blockchain is apparent to everybody that is available on the chain this makes the information weak which is anything but an ideal result for a decentralized stage.